A CROSS-SECTIONAL STUDY ON PATIENTS AND HEALTH FACILITY CHALLENGES FACED BY FRONTLINE NURSE MANAGERS DURING THE COVID-19 PANDEMIC AT KAWEMPE NATIONAL REFERRAL HOSPITAL, KAMPALA DISTRICT. - Likico OPU, Emily; Birungi, Dr. Elisha (Student's Journal of Health Research Africa, 2025)
Background. Healthcare workers' health, well-being, and safety are paramount to a functioning healthcare system and to ensuring patient safety. Consequently, it is necessary to mitigate risks on multiple levels. This study determined the challenges faced by frontline nurse managers during the COVID-19 pandemic at Kawempe National Referral Hospital, Kampala District. Methodology. A descriptive cross-sectional study design and quantitative data collection method was used, 30 respondents were selected using convenience sampling procedure. Data was collected using questionnaires. Data was analyzed using excel data base and the results were presented inform of figures and tables. Results 20 (66.7%) of the respondents were Midwives, and 18 (60%) of the respondents had 5 years or more of experience. 21 (70%) reported poor health-seeking behavior of patients due to fear of COVID-19 infection from hospitals, 30 (100%) reported patients’ failure to adhere to recommendations, and 30 (100%) reported lack of appreciation from patients and community members. Facility-related challenges included; 30 (100%) of participants reported, increased exposure to highly contagious, life-threatening infections, 18 (60%) reported a lack of support, supervision, and monitoring, 30 (100%) reported a lack of resources such as oxygen, 30 (100%) reported lack of equipment such as beds to handle the number of patients and 25 (83.3%) reported excessive job demands as well as heavy workload. Conclusion. The established patients and health facility-related challenges included; poor health-seeking behavior of patients due to fear of covid 19 infection from hospitals, lack of appreciation from patients and community members, increased exposure to highly contagious, life-threatening infections, and lack of support, supervision, and monitoring. Recommendations. The administration of Kawempe National Referral Hospital should endeavor to provide all the required resources, such as beds, PPE, and equipment, to ensure the provision of high-quality, efficient services.